Commodity risk assessment of Acer palmatum plants grafted on Acer davidii from China. (12th May 2022) - ,; Bragard, Claude; Baptista, Paula; Chatzivassiliou, Elisavet; Di Serio, Francesco; Jaques Miret, Josep Anton; Justesen, Annemarie Fejer; MacLeod, Alan; Magnusson, Christer Sven; Milonas, Panagiotis; Navas‐Cortes, Juan A; Parnell, Stephen; et al.
Abstract: The European Commission requested the EFSA Panel on Plant Health to prepare and deliver risk assessments for commodities listed in Commission Implementing Regulation (EU) 2018/2019 as 'High risk plants, plant products and other objects'. This Scientific Opinion covers plant health risks posed by 2‐year‐old bare rooted plants for planting of Acer palmatum grafted on rootstocks of Acer davidii imported from China to the EU, taking into account the available scientific information, including the technical information provided by China. All pests associated with the commodity were evaluated against specific criteria for their relevance for this Scientific Opinion. Twenty‐two pests that fulfilled all relevant criteria were selected for further evaluation. For 20 pests, the risk mitigation measures described in the technical dossier from China were evaluated taking into account the possible limiting factors. For these pests, an expert judgement is given on the likelihood of pest freedom taking into consideration the risk mitigation measures acting on the pest, including uncertainties associated with the assessment. While the estimated degree of pest freedom varied among pests, Lopholeucaspis japonica was the pest most frequently expected on the commodity. The Expert Knowledge Elicitation indicated, with 95% certainty, that 9, 336 or more bare rooted plants per 10, 000 will be free from L. japonica . For Anoplophora chinensis and Anoplophora glabripennis, the Panel considers that China applies the relevant measures as specified in Commission Implementing Decision (EU) 2012/138 and Commission Implementing Decision (EU) 2015/893.